Metode Penfatwaan Jawatankuasa Fatwa Negeri Perak: Analisis Terhadap Fatwa-Fatwa Negeri Perak Dari Tahun 2016 Hingga 2019 - Sabri, Muhammad Nazirul Mohd (2024)
The Perak State Fatwa Committee (JFNPk) is a religious institution with full of jurisdictions and authority to decide and issue fatwas in the state of Perak based on its own methodology (manhaj). However, research has found that some of the fatwas issued by JFNPk differ in methodology from those of other states, lack uniformity in the fatwa-issuing methods, and are heavily bound to the Shāfi'ī school of law. Therefore, this study aims to identify the basic fatwa-issuing methodologies among Islamic scholars. Subsequently, it examines the methodologies applied by JFNPk by referring to several fatwas from the years 2016 to 2019 as case studies. The study also analyzes the fatwas that have been decided in terms of their fatwa-issuing methods. The methodology of this study uses a qualitative approach by analyzing content, wherein data collection methods, interviews, documentation, and data analysis are presented descriptively. As a result, this study shows that the practice of issuing fatwas by JFNPk follows the fatwa-issuing methodologies established by Islamic scholars. The study also found that there are several methodological aspects that need improvement, especially regarding the authority of sources in the process of istidlāl (derivation of legal rulings). Subsequently, this study suggests the creation of a standardized guideline module for issuing fatwas, as uniformity in methodology can ensure the quality of fatwa research and public trust.